A preliminary continental risk map for malaria mortality among African children. - Snow, R; Craig, M; Deichmann, U; le Sueur, D (1999)
Approaches to global public health are increasingly driven by an understanding of regional patterns of disease-specific mortality and disability. Current estimates of disease risks associated with Plasmodium falciparum in sub-Saharan Africa remain poorly defined. Through the integration of high-resolution population and climate probability models of P. falciparum transmission, geographical information systems have been used to define the spatial limits of populations exposed to the risk of infection in Africa. These estimates were combined with a range of annual malaria-specific mortality rates, derived from a variety of epidemiological approaches, among children aged 0-4 years. The best estimates of malaria-attributable mortality using this approach ranged between 0. 43 million and 0.68 million deaths per annum among an exposed population of approximately 66 million children in 1990. Despite the limitations of modelled transmission and population distributions, these empirical approaches to probabilities of infection risk and epidemiological data on mortality provide a novel approach to present and projected burdens of malaria mortality, as discussed here by Bob Snow, Marlies Craig, Uwe Deichmann and Dave le Sueur.